Pengaruh Persepsi Kemudahan, Persepsi Manfaat Dan Fitur Layanan Terhadap Minat Menggunakan E-Wallet Pada Aplikasi Dana (Studi Kasus Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2019) - Eka Dewi Fitriyanti; Eka Farida; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect of perceived convenience, perceived benefits and service features on the interest in using e-wallets in the DANA study application for students of the Faculty of Economics & Business class of 2019, Islamic University of Malang. The type of research used is quantitative. The research sample was taken by purposive sampling technique with the Malhotra formula used to take the sample, namely the number of items x 5 so that the total sample is 85 respondents. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. Testing the data used is testing the simultaneous hypothesis (Test F) and testing the partial hypothesis (Test t). The results of his research show that perceived convenience partially has no effect on interest in using e-wallets. Perceived benefits partially have no effect on interest in using e-wallets. Service features have a significant and positive influence on interest in using e-wallets. Meanwhile, simultaneously perceived convenience, perceived benefits and service features have a significant effect on interest in using e-wallets. Keywords: Perceived Convenience, Perceived Benefits, Service Features, and Interest in Using E-Wallet